The Effect of Skipping Exercises in Increasing Cardiovascular Endurance of Running Athletes in Bone Bolango Regency - Hunta, Mohamad Akil; Duhe, Edy Dharma Putra; Haryanto, Arief Ibnu (Jurnal Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of skipping exercises on improving cardiovascular endurance among running athletes in Bone Bolango Regency. The research employs a quasi-experimental design with a pretest-posttest approach. The study involved nine athletic athletes as participants, who were subjected to skipping exercises over a specified training period. The cardiovascular endurance of the athletes was measured using the Bleep Test before and after the intervention. Data analysis included normality tests, homogeneity tests, and t-tests to determine the statistical significance of the results. The findings indicate a significant improvement in the athletes' cardiovascular endurance, as demonstrated by increased VO₂ max values after the skipping exercise program. The t-test results showed that skipping exercises have a statistically significant impact on cardiovascular endurance (Tcount = 23.263 Ttable = 2.306, P-Value = 0.00 0.05). These results suggest that skipping exercises can serve as an effective and practical training method to enhance cardiovascular endurance in running athletes.